Performance of Ralumac Micro Surfacing at LATAR Highway - Muhamad, Rahimah; Salleh, Shamsuni; Abdillah, Mohd Haryazi; Ahmad Shahimi, Ahmad Fuad (Journal of Advanced Research in Applied Mechanics, 2020)
Maintaining pavement to desired level of serviceability as required by Malaysian Highway Authority (MHA) give immense pressure to highways operators. Pavement distress such as roughness, rutting and cracking are common problems that occur after the highway has been operational. Pavement preservation has been sought as a potential alternative for managing all the pavement distress. This paper evaluates the performance of Ralumac Micro surfacing at accident prone areas KM23.7 Eastbound, KM8.5 Eastbound, Puncak Alam Interchange PA-D and Puncak Alam Interchange PA-A, LATAR Highway. The evaluation comprises of International Roughness Index (IRI), rutting, texture depth, Pavement Condition Index (PCI) and skid resistance. The result revealed that Ralumac Micro surfacing system has significant improvement on pavement condition thus very effective for reducing traffic accidents due to skidding. It performed better at downhill area, uphill area and interchange ramps.